A comparative study by leg (weak - strong) and its relationship to strongly and accuracy jump shooting for corner in handball - Mousa, Mahmoud; Mahmood, Mohammed; Hamza, Mohammed (Journal of Physical Education, 2015)
Handball is a team sport and be one of fast games in passing or shooting. The team with most goals is the winner. The aim of the sport is to throw the ball in the opponent team goal. There are many skills in handball like catching, passing, dribbling, and shooting is the important skill because if not score all skills not benefits. The aim of this research is to know the difference between shooting by jumping on the corner by leg (weak, strongly) in handball. Also to know the relationships between jumping shooting on corner by leg (weak, strongly) with force and accuracy shooting in handball to fist class plyers on Iraq. The hypotheses of the research that there is deference Statistical between jumping shooting on corner by leg (weak, strongly) also there is many relationships between jump shooting on corner by weak leg with accuracy shooting in handball. The main conclusion that Achieveall The Hypotheses of this Research and all the players Adoption strongly legs to shooting nor adoption many substitute way to jump shooting like weak legs to feak the opponents in defensive that lead the teams not scorer many goals in match